The Ghosts of the Past: Hermeneutical Reflections on Historical Criticism within a Shared Conversation on Human Sexuality - Sargent, Benjamin (The expository times, 2016)
This article is a reflection on the ways in which scripture was approached by participants within one of the Church of England’s Shared Conversations on Human Sexuality. It notes the significance of historical-critical hermeneutical concepts within the conversation and concludes that the hermeneutical aspect of the debate on scripture and sexuality, as carried out within the context of the shared conversations, is far removed from the scholarly discussion of theological hermeneutics for which the issue of human sexuality has been a great stimulant.